P79 The prevalence and correlates of tobacco smoking in irish university students, focusing on social smoking and self-identification of smokers; a cross-sectional study. (3rd September 2019) - O'Mahony, C; Perry, IJ
Abstract : Background: Social smoking is becoming increasingly common, emerging as a separate and distinct pattern of smoking behaviour to regular smoking. Smoking denial, too, has become more prevalent, with those who engage in smoking behaviour often not self-identifying as smokers. This study aims to examine the prevalence of smoking and social smoking in Irish university students and the self-identification of same, along with assessing other factors for any association the may have with smoking behaviour, namely smoking identity, frequency of tobacco consumption and alcohol and drug use. Methods: A cross-sectional study was carried out in the form of a web questionnaire distributed to undergraduate students of University College Cork (UCC). 1, 606 initial responses were collected. Exclusion criteria were applied, removing graduate students, those who had incorrectly completed the questionnaire and a small number of duplicates, yielding a final sample size of 1, 434 and a final response rate of 10.4%. Data were analysed using IBM SPSS software and the method of analysis included both chi-square testing and multinomial logistic regression analyses. Results: 58.2% (n=834) of respondents are smokers with 77.2% (n=644) of those being social smokers. Social smoking has significant associations with a number of smoking characteristics including decreased frequency of habit (OR=0.084; 95% CI=0.044–0.160; p <0.001), sourcing tobacco from others (OR=2.211; 95% CI=1.401–3.489; p <0.001), less inclination to quit (OR=0.426; 95% CI=0.231–0.792; p =0.007) and being influenced to smoke while drinking (OR=3.698; 95% CI=1.461–9.362; p =0.006) or if others are smoking (OR=3.085; 95% CI=1.495–6.365; p =0.002). While 76.8% of regular smokers self-identified as smokers, only 12.3% of social smokers self-identified as smokers (OR=0.078, 95% CI=0.040–0.153; p ≤0.001). Smoking in general is associated with substance use and misuse (OR=2.754; 95% CI=1.613–4.705; p <0.001) in comparison to non-smokers. Conclusion: Social smoking is a prevalent behaviour in university students and constitutes the majority of smoking behaviour amongst those surveyed. The difference in results between social smoking and regular smoking groups reinforces that social smoking is a distinct smoking pattern. There is a vast discrepancy in the self-identification of smokers and their smoking behaviour, more so amongst social smokers than regular smokers. Limitations of this study included low response rate and potential for self-selection bias. Further study could be carried out in this area with regards to smoking interventions and potential need to target these groups specifically in public health campaigns.